Trilock Brick : Inovasi Desain Batako Bentuk Segitiga dengan Sistem Interlock - Ningtiyas, Ubbidah Agus (Civil Infrastructure Engineering and Architectural Design, 2024)
As the construction industry in Indonesia continues to grow, it has significantly impacted the demand for building materials, particularly in the construction sector. One such material is